2016
DOI: 10.1038/hdy.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect genetic effects of sex-specific mitonuclear epistasis on reproductive ageing

Abstract: Mitochondria are involved in ageing and their function requires coordinated action of both mitochondrial and nuclear genes. Epistasis between the two genomes can influence lifespan but whether this also holds for reproductive senescence is unclear. Maternal inheritance of mitochondria predicts sex differences in the efficacy of selection on mitonuclear genotypes that should result in differences between females and males in mitochondrial genetic effects. Mitonuclear genotype of a focal individual may also indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 52 publications
2
51
1
Order By: Relevance
“…Another D. melanogaster study recovered a significant effect of male partner identity on female fecundity, consistent with a male IGE affecting female fitness components (Tennant et al 2014). Male IGEs affecting female fecundity appear to be exerted through male mitonuclear epistasis in seed beetles (Callosobruchus maculatus), suggesting a complex interplay between organelle-specific IGEs and sexual conflict (Immonen et al 2016).…”
Section: Empirical Evidence For Iges In Behavioral Ecology Researchmentioning
confidence: 93%
“…Another D. melanogaster study recovered a significant effect of male partner identity on female fecundity, consistent with a male IGE affecting female fitness components (Tennant et al 2014). Male IGEs affecting female fecundity appear to be exerted through male mitonuclear epistasis in seed beetles (Callosobruchus maculatus), suggesting a complex interplay between organelle-specific IGEs and sexual conflict (Immonen et al 2016).…”
Section: Empirical Evidence For Iges In Behavioral Ecology Researchmentioning
confidence: 93%
“…Same-aged mated and virgin beetles were kept individually for 24 h with beans, after which they were snap-frozen with liquid nitrogen and stored in −80°C. This time point was chosen as it corresponds to the time when females lay most of their eggs (Fox 1993; Immonen et al. 2016a) and males still undergo increased postmating metabolism, presumably due to ejaculate renewal (Immonen et al.…”
Section: Methodsmentioning
confidence: 99%
“…neutral and nonfunctional. This view contrasts with an increasing number of recent studies that have shown that naturally occurring mitochondrial DNA (mtDNA) haplotypes affect ageing and lifehistory phenotypes (e.g., James and Ballard 2003;Ellison and Burton 2006;Maklakov et al 2006;Rand et al 2006;Ballard et al 2007a;Clancy, 2008;Dowling et al 2009;Arnqvist et al 2010;Immonen et al 2016).…”
mentioning
confidence: 87%